Penetration Depth Local Effect of Impactors on Concrete Structures - K. S. Al-Hachamee, Eyad; A. A. Al-Quraishi, Hussain (Journal of Engineering and Sustainable Development, 2010)
Available formulae for predicting the penetration depth of concrete structures impacted by a solid missile are summarized and reviewed. Based on a statistical analysis of existing data, a new formula has been proposed for predicting the penetration depth of concrete structures due to impact by solid missiles. The new equation for the penetration depth of concrete structure impacted by solid missiles is applied for non-reinforced concrete structures, which gives a good result with experimental study and is compared with other research results to check its validity, this equation includes missile parameters which are the weight of missile(W), the diameter of missile (d), Velocity of missile(V) and Target parameters which are concrete member thickness (t), and concrete member strength (fc').